Ring substituted 3-phenyl-1-(2-pyrazinyl)-2-propen-1-ones as potential photosynthesis-inhibiting, antifungal and antimycobacterial agents - Opletalová, Veronika; Hartl, Jirí; Patel, Asmita; Palát, Karel; Buchta, Vladimir (Farmaco (Societa chimica italiana, 2002)
Four series of ring substituted (E)-3-phenyl-1-(2-pyrazinyl)-2-propen-1-ones were prepared by means of modified Claisen-Schmidt condensation of acetylpyrazines with aromatic aldehydes. The structures were confirmed by elemental analysis, IR, 1H NMR and 13C NMR spectra. The compounds were tested for specific biological properties and some derivatives exhibited photosynthesis-inhibiting, antifungal and antimycobacterial properties. The most pronounced effects were observed with compounds substituted with phenolic groups. Ortho-hydroxyl substituted derivatives were more potent than the corresponding para-hydroxyl substituted analogues.
Keywords: herbicidy; molekulární konformace; Mycobacterium tuberculosis; Antifungal Agents; antituberkulotika; mikrobiální testy citlivosti; houby; Molecular Structure; Structure-Activity Relationship; Photosynthesis; Heterocyclic Compounds; fotosyntéza; Molecular Conformation; heterocyklické sloučeniny; Fungi; magnetická rezonanční spektroskopie; molekulární struktura; Microbial Sensitivity Tests; vztahy mezi strukturou a aktivitou; Antitubercular Agents; Magnetic Resonance Spectroscopy; antifungální látky; Herbicides